Výchova kněží a jejich působení na přelomu 18. a 19. století - Nešpor, Zdeněk R. (Lidé města, 2006)
Activities of priests constituted an important (although definitely not exclusive) source of popular religious attitudes and notions. At the end of early modern times, popular-religious readings and schools also exhibited more marked influence. These institutions played their role not only in passing of contemporary religious reforms but also (and primarily) during their changes. For this reason, the author monitors enlightened reforms of instruction of future priests in Hapsburg countries which headed explicitly towards transformation of their work; originating in the Van Swieten’s reform in 1750s, continued by the Rautanstrauch’s reform of 1774, introduction of general seminars and other changes of Joseph II, until their changes during the reign of Leopold II (1791). One of the most important events was the institutionalization of pastoral theology which symbolically replaced former polemical theology. The article also analyses, in more detail, the first Czech text books on this subject written by Strahov’s Premonstratensian J. Chládek and F. Giftschütz (translated by V. Stach). Architects of these reforms were interested in transformation of popular Christianity in the direction of unpretentious ethical and social understanding of religious belief; they were inspired in many respects by protestant theologians, resulting also in more positive reception of Hussitism in the Bohemian lands. In the first half of the 19 th century, these trends were reflected also in popular religiosity, hand in hand with national agitation of many Catholic clergymen although not always as intended by their originators. The revived Czech nation often expressed disapproval of their own regenerators, fact which the Catholic clergy countered (rather unsuccessful in long term) with an attempt of new confesionalization.